Long‐term fluctuations and mechanisms of seed production of riparian tree canopy species. Issue 3 (31st March 2023) - Sakio, Hitoshi; Kon, Ayumi; Kubo, Masako; Nakano, Yosuke
Abstract: Annual seedfall was measured over a 24‐year period for three canopy species, Fraxinus platypoda, Pterocarya rhoifolia, and Cercidiphyllum japonicum, in a riparian forest in the Chichibu Mountains, central Japan. We collected seeds from 20 traps approximately every month, except in the winter. Fraxinus platypoda and P. rhoifolia seedfall fluctuated, with a 2‐year cycle. The seedfall of C. japonicum also fluctuated, but this species produced seeds every year, with an approximate 4‐year cycle. The simple moving average over 5 years for F. platypoda and P. rhoifolia was maintained at a constant level over the 24‐year period, but it gradually increased for C. japonicum . Each year's seedfall for the three species was influenced by the previous year's seedfall. The results for F. platypoda suggest that the fluctuations in the amount of seedfall were almost entirely dependent on fluctuations in stored resources, regardless of the previous year's weather. Conversely, the amount of seedfall for P. rhoifolia and C. japonicum was influenced by fluctuations in stored resources and the average temperature or precipitation in the summer of the year before flowering. These differences in seed production patterns were associated with differences in life history characteristics such as seed size and regeneration mechanisms. Abstract : This study has revealed masting in three riparian tree species over a 24‐year period. Fraxinus platypoda and Pterocarya rhoifolia showed a clear fluctuation of seedfall with a 2‐year cycle. Cercidiphyllum japonicum also had fluctuation of seedfall, but produced seed every year with approximate 4‐year cycle. The fluctuations of seedfall of F. platypoda are dependent on fluctuations in stored resources. Conversely, the seedfall of P. rhoifolia and C. japonicum are dependent on fluctuations in stored resources and the temperature in summer of the year before flowering.